Al-Siyasah al-Shar‘iyyah’s consideration and its approach among the governors in Islamic financial institutions: a Malaysian’s experience - Mahmad Robbi, Ahmad Akram; Ishak, Muhammad Shahrul Ifwat; Asni, Fathullah (Emerald Publishing Limited, 2024)
Purpose – Islamic financial institutions (IFIs) in Malaysia continue to promote Shari‘ah-compliant business and transactions. As a result, the governors have a lot to think about before issuing any fatwa or ordinance, which impacts the majority of Malaysians. Nevertheless, the point of views from the governors have not been highlighted much. This research seeks to investigate the extent to which the conception of al-Siyasah al-Shar‘iyyah is embraced by Shari‘ah committees’ leadership roles within IFIs. The importance of al-Siyasah al-Shar‘iyyah in decision-making makes abandoning the Shari‘ah principle untenable and its significant role for IFIs in Malaysia cannot be overstated. It serves as a crucial tool for decision-making by authorities and governors.